2021
DOI: 10.3390/cryst11101166
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Protein Crystallization Additives

Abstract: Among its attributes, the mythical philosopher’s stone is supposedly capable of turning base metals to gold or silver. In an analogous fashion, we are finding that protein crystallization optimization using ionic liquids (ILs) often results in the conversion of base protein precipitate to crystals. Recombinant inorganic pyrophosphatases (8 of the 11 proteins) from pathogenic bacteria as well as several other proteins were tested for optimization by 23 ILs, plus a dH2O control, at IL concentrations of 0.1, 0.2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…It was also reported that for a long storage period of 72 h at −80 °C, hMBCOMT still presents an increment of 27% on its original activity recovery. Moreover, if 4 °C was considered to preserve the protein, the addition of low concentrations of [Ch][DHP] maintained the enzyme’s biological activity for 48 h. Therefore, this stabilization formulation can favor later crystallization and bio-interaction trials, while disfavoring the precipitation of the additives present at higher concentrations [ 48 ]. Herein, and for the soluble isoform hSCOMTVal108-6His, both 4 and −80 °C temperatures were evaluated after a period of 72 h of storage ( Table 1 ) using protein samples solubilized in both Buffer A and Buffer B with and without glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that for a long storage period of 72 h at −80 °C, hMBCOMT still presents an increment of 27% on its original activity recovery. Moreover, if 4 °C was considered to preserve the protein, the addition of low concentrations of [Ch][DHP] maintained the enzyme’s biological activity for 48 h. Therefore, this stabilization formulation can favor later crystallization and bio-interaction trials, while disfavoring the precipitation of the additives present at higher concentrations [ 48 ]. Herein, and for the soluble isoform hSCOMTVal108-6His, both 4 and −80 °C temperatures were evaluated after a period of 72 h of storage ( Table 1 ) using protein samples solubilized in both Buffer A and Buffer B with and without glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids, which are composed of cations and anions, are liquid molten salts at room temperature. Owing to their advantages of low volatility, high viscosity and thermal stability, and excellent solvation ability and ionic strength, ionic liquids have been used as solvents or additives during the crystallization process . It is worth noting that several ionic liquids can be recurrently used for the polymorph control of API.…”
Section: Novel Techniques For Preparation and Regulation Of Drug Poly...mentioning
confidence: 99%
“…The first was the choline-based IL, which was extensively studied to reveal whether it promotes or inhibits protein aggregation and protein stabilization, with its outcome being IL concentration dependent [28,46,47]. The second was the imidazolium-based IL, which was employed as a co-solvent or an additive for protein crystallization as shown by the group in the stabilization of periplasmic molybdenum aldehyde oxidoreductase (PaoD) protein in the presence of [C4mim]Cl, with its effect being alkyl chain-length dependent [32,48]. Moreover, as shown in Table 1, beyond the study of the two different cation classes, we also analyzed a wide range of IL concentrations, between 5 to 500 mM and with different anion paring, since both cationic and anionic parts of IL can play an important role in protein stabilization [35].…”
Section: Preliminary Studies For Hmbcomt Stabilizationmentioning
confidence: 99%